EFEKTIVITAS METODE EKSPERIMEN DENGAN PENERAPAN MODEL STUDENT FACILITATOR AND EXPLAINING (SFE) DALAM PEMBELAJARAN FISIKA DI KELAS VII SMPN 3 SINGINGI HILIR - Dwi RaraWarapsari; M. Rahmad '; Hendra Sudrajat (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: This research is aimed to know the effectiveness with experiment learning method by using student facilitator and explaining model and the class which used conventional method in learning physics. This research belongs to Quasi Experimental research with Intact Group Comparison Program. The sample of this research was the first year students of SMPN 3 Singingi Hilir, which consisted of 55 students and divided into 2 classes: experimental and control class. The data of this research belongs to student collectivity and the results of the study after physics learning by using student facilitator and explaining model which analyzed descriptively and inferentially. Based on data analysis, students’ activity in experimental class was in a very good category. The students’ ability averagely as 81% was in effective category, while in the control class was in good category and the students’ ability averagely as 72% also in effective category. Based on the output independent sample t-test was concluded thitung> t table (3.007> 1.675) means that there are significant differences in learning outcomes of students with a class that uses experimental methods facilitator and student learning model explaining the conventional experimental learning classes It can be concluded that experiment method by using student facilitator and explaining model was effective in physics learning in the first year students of SMPN 3 Singingi Hilir.